Logical Fallacy Dan Pertentangan Moral Dalam Pembebasan Narapidana Di Era Pandemi Covid-19 - Yulia Nizwana (Riau Law Journal, 2021)
The global COVID-19 pandemic has created new problems for nation-states, especially regarding how the country's efforts to prevent and stop the spread of this virus from spreading further. Socializing the Social Distancing movement is one of the steps taken by the Government of Indonesia as a disaster emergency status issued from February 29, 2020 to May 29, 2020 regarding this virus pandemic with a total time of 91 days. In addition, starting on March 31, 2020, the Indonesian government has also implemented a policy of releasing prisoners through an assimilation and integration program, with the aim of breaking the chain of Covid-19 transmission, on the grounds that the number of inmates who are already over capacity will have a great potential for the spread of Covid-19. The emergence of the pros and cons of the government's policy on the release of prisoners in the midst of the Covid-19 pandemic indicates that there is something wrong with the policy, because there is no guarantee and measure so far, everyone who has been released from prison will behave well and do not threaten the safety of many people in the future and touch the sense of community justice so that there is a moral conflict in the community. The logical fallacy (misguidance of thinking) and the moral conflict of the prisoner release policy in the midst of the Covid-19 pandemic is a formal error that occurs due to a violation of logical principles regarding legal policy on the release of prisoners in the Covid-19 pandemic era which was taken by the government for humanitarian reasons to break the chain of the spread of Covid-19 because the number of inmates who have overcapacity has a great potential for Covid-19 transmission. So that prisons do not overcapacity, there are things that have not been corrected by policymakers in Indonesia, because so far government policies have prioritized prison sentences in law enforcement even though prisons are not the estuary for all those who commit crimes, not all prisoners must be imprisoned, Those who must be imprisoned should be those that are in direct contact with or violate the rights of other people so that it is certain that the prison will not be overcapacity. The policy of releasing prisoners to prevent the transmission and spread of Covid-19 is not the right solution and is only temporary. So that what happened was not saving many people, but threatening to increase the crime rate after the release of prisoners in the midst of the Covid-19 pandemic.